(untitled) (Kairaranga, 2010)
Primary teacher training programmes in New Zealand do not provide training about specific communication disorders (SCDs), despite prevalence of SCDs of approximately 7%. This pilot study investigated the effectiveness of a three-hour professional development (PD) programme for a specialised group of primary teachers, Special Education Needs Coordinators (SENCOs), around working with children with SCDs in the classroom. Six SENCOs from different schools participated. Effectiveness was measured using a pre-test/post-test within-subjects design. Outcome measures were (1) a knowledge questionnaire and (2) a videoed interaction with a new-entrant child. SENCOs increased the specificity of responses to open questions and improved their scores on closed questions, with a significant improvement in knowledge about characteristics of the children. Eleven strategies were counted in the videoed interactions; seven improved and two deteriorated. SENCOs reported satisfaction with programme content and length. Additional research is recommended to further develop the PD programme into an effective resource for classroom teachers.